Methodological approach to evaluate multihazard risk on bridges and viaducts - castorani, Antonio; di santo, Antonio Rosario; fratino, Umberto; limongelli, Roberto; mezzina, Mauro; pagano, Alessandro; raffaele, Domenico; trulli, Isabella (Italian journal of engineering geology and environment, 2011)
<span data-sheets-value="{"1":2,"2":"According to the usual definition, risk is a combination of Hazard, Exposure and Vulnerability, representing the global damage amount connected to a particular event that may occur in a given area in a prefixed return time. According to the previous definition, a “multihazard risk analysis” needs a methodological approach able to combine in terms of effects several different natural events that may occur in an area. This analysis has the purpose of defining political and technical programs for risk mitigation, so to address public resources where priorities are high. Bridges play a primary role in the development and application of such analysis, showing high vulnerability towards great natural hazards such as floods and seismic actions.\rIn this paper the results of a multi hazard analysis carried out taking into account seismic and hydraulic hazards on bridges in Capitanata region (FG - Puglia Region, South Italy) are presented. This work has been developed in a research project, named “Studio di Fat- tibilità per il Monitoraggio e la Messa in Sicurezza delle Aree Urbane a Rischio di Stabilità Statica e Vulnerabilità Strutturale nella Città e Provincia di Foggia” managed by the Autorità di Bacino della Puglia together with the Technical University of Bari.\rThe proposed approach is based on the definition of a synthetic Index, named Priority Index, that simply defines the global risk level associated. It summarizes several information connected to the main structure properties, related to seismic and hydraulic local effects, to the exposition and to the functionality. The Seismic Damage Index is strictly connected to the structural behavior and its response to seismic actions expected in the well defined area. It compares the spectral acceleration representing the site design spectrum with two other spectral acceleration values considered equivalent to Hazus median damage function accelerations, corresponding to slight damage and complete damage for the structure. The Hydraulic Damage Index furnishes a quantitative information on the bridge behavior with respect to floods, and it is dependent on geometrical characteristics of the bridge cross section and on climatic and geomorphological properties of the river watershed. It compares the expected flow at a fixed return time with the maximum hydraulic capacity of the bridge cross section. The Functionality Index is connected to the exposition of the structure being not dependent from the specific hazard analyzed. It summarizes information such as road class, expected traffic levels and bridge length to define a sort of hierarchical classification of the investigated structures."}" data-sheets-userformat="{"2":13057,"3":{"1":0},"11":0,"12":0,"15":"Arial","16":10}">According to the usual definition, risk is a combination of Hazard, Exposure and Vulnerability, representing the global damage amount connected to a particular event that may occur in a given area in a prefixed return time. According to the previous definition, a “multihazard risk analysis” needs a methodological approach able to combine in terms of effects several different natural events that may occur in an area. This analysis has the purpose of defining political and technical programs for risk mitigation, so to address public resources where priorities are high. Bridges play a primary role in the development and application of such analysis, showing high vulnerability towards great natural hazards such as floods and seismic actions. In this paper the results of a multi hazard analysis carried out taking into account seismic and hydraulic hazards on bridges in Capitanata region (FG - Puglia Region, South Italy) are presented. This work has been developed in a research project, named “Studio di Fat- tibilità per il Monitoraggio e la Messa in Sicurezza delle Aree Urbane a Rischio di Stabilità Statica e Vulnerabilità Strutturale nella Città e Provincia di Foggia” managed by the Autorità di Bacino della Puglia together with the Technical University of Bari. The proposed approach is based on the definition of a synthetic Index, named Priority Index, that simply defines the global risk level associated. It summarizes several information connected to the main structure properties, related to seismic and hydraulic local effects, to the exposition and to the functionality. The Seismic Damage Index is strictly connected to the structural behavior and its response to seismic actions expected in the well defined area. It compares the spectral acceleration representing the site design spectrum with two other spectral acceleration values considered equivalent to Hazus median damage function accelerations, corresponding to slight damage and complete damage for the structure. The Hydraulic Damage Index furnishes a quantitative information on the bridge behavior with respect to floods, and it is dependent on geometrical characteristics of the bridge cross section and on climatic and geomorphological properties of the river watershed. It compares the expected flow at a fixed return time with the maximum hydraulic capacity of the bridge cross section. The Functionality Index is connected to the exposition of the structure being not dependent from the specific hazard analyzed. It summarizes information such as road class, expected traffic levels and bridge length to define a sort of hierarchical classification of the investigated structures.